2017
DOI: 10.1590/1807-3107bor-2017.vol31.0022
|View full text |Cite
|
Sign up to set email alerts
|

Longevity of metal-ceramic crowns cemented with self-adhesive resin cement: a prospective clinical study

Abstract: Resin cements are often used for single crown cementation due to their physical properties. Self-adhesive resin cements gained widespread due to their simplified technique compared to regular resin cement. However, there is lacking clinical evidence about the long-term behavior of this material. The aim of this prospective clinical trial was to assess the survival rates of metal-ceramic crowns cemented with self-adhesive resin cement up to six years. One hundred and twenty-nine subjects received 152 metal-cera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 20 publications
0
15
1
2
Order By: Relevance
“…These monomers can promote bonding to metallic ions through an acid-base reaction [4]. This additional chemical adhesion of self-adhesive resin cements and their easy application, which does not require dentin treatment before, gained widespread use of self-adhesive resin cements in cases with minimal presence of coronal tissue [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These monomers can promote bonding to metallic ions through an acid-base reaction [4]. This additional chemical adhesion of self-adhesive resin cements and their easy application, which does not require dentin treatment before, gained widespread use of self-adhesive resin cements in cases with minimal presence of coronal tissue [3].…”
Section: Discussionmentioning
confidence: 99%
“…This study presented a case report with a time of observation of 2 years, and although it can be considered a short follow-up period, there are few case reports available in the literature that describe the self-adhesive cementation of cast post and cores. Some studies evaluated the self-adhesive cementation of metal ceramic crowns and found survival rates higher than 90% after six years of follow-up [3,5], which may indicate the clinical success of adhesion of self-adhesive resin cements on metal substrates. The use of cast post and core associated with self-adhesive cement may offer a reliable rehabilitation choice, with user-friendly technique, low film thickness and adhesion to dentin walls and to the metal.…”
Section: Discussionmentioning
confidence: 99%
“…Nesse estudo foram testados dois cimentos resinosos amplamente utilizados na Odontologia, um convencional e outro autoadesivo. A hipótese apresentada no presente estudo foi negada, uma vez que os resultados mostraram que não houve diferenças estatisticamente significantes entre os cimentos testados nos diferentes tempos de armazenamento, o que corrobora com os resultados obtidos em outros estudos (14)(15).…”
Section: Discussionunclassified
“…A sufficient and clinically reliable bond between dental tissues and restorations is a crucial precondition for resin bonded partial crowns, crowns, and bridges [1]. Self-adhesive resin cements (SARCs) have shown promising clinical outcomes resulting in a survival rate of 97.6% over 6 years for metal-based crowns, a survival rate of 83.5% for lithium disilicate crowns over 10 years and survival rates of above 90% for zirconia fixed dental prostheses over 6 years [2][3][4]. SARCs are designed to combine the ease of use of glass ionomer cements and the favorable mechanical and adhesive properties of conventional resin cements in combination with a beforehand applied adhesive system (CRC+SE) [5].…”
Section: Introductionmentioning
confidence: 99%